Establishment of a national catastrophe burn plan for the delivery of care for burn patients in Lebanon - Moufarrij, Sarah; Deghayli , L; Frangieh , M; Assaad , S; Souaiby, . (Mediterranean Journal of Emergency Medicine, 2021)
Objective: This study aims at gathering data concerning the care of burn patients in Lebanon. Based on the findings, a national burn plan will be drafted to standardize burn treatment. Methods: Questionnaires were distributed to physicians in four hospitals, emergency medical team responders in two Lebanese Red Cross centers, the Lebanese Army and the Lebanese Civil Defense with the approval of the Lebanese Society of Emergency Medicine and the Syndicate of Hospitals, after obtaining informed consent. The questions covered topics including burn treatments, patient triage, burn wound evaluation, and the perceived role of the different parties involved in dealing with a burn catastrophe. A retrospective burn patient chart review was conducted at the American University of Beirut Medical Center in order to better understand the epidemiology of burns in the country Results: A total of 97 questionnaires were distributed, 58 were collected from various hospitals throughout Lebanon and 39 were collected from various respondents, 140 charts were reviewed from the American University of Beirut’s medical records department. When asked to define a “severe burn”, the only hospital that answered with internal consistency is Nabatieh hospital, choosing “< 10% of total body surface area (TBSA)” to define a severe burn in adults and “20% TBSA” to define it in the pediatric population. When asked about the most important first step when dealing with a burn patient, 32% of responders from the Lebanese Red Cross in Spears correctly identified fluid resuscitation as the first step in management, whereas no responder from the Lebanese Red Cross in Tripoli chose this answer. The medical charts reviewed from the American University of Beirut showed that the most common type of burn was the thermal burn (84.1%). Only 2.3% of patients got treated at the site of the accident and 3.8% of patients went on to get treated at a burn hospital after being seen at the American University of Beirut. Conclusion: In Lebanon, burn care appears to be fragmented and heterogeneous, in addition to the fact that the different parties (Army, Lebanese Red Cross, Civil Defense and physicians), that should sequentially be involved in addressing burn care, seem unsure of their role in the chain of command. Centralization of burn care by means of a national catastrophe burn plan would allow for a multi-disciplinary and coordinated approach, which is the only effective way of treating a burn victim.